AS MALDIÇÕES DO SALMO 137: O princípio da reciprocidade na justiça do Antigo Testamento como chave bíblica para a interpretação - Gusso, Antônio Renato (2007)
This thesis, based on exegesis, defends the position that the curses in Psalm 137 should be interpreted by taking into account the principle of reciprocity which belongs to the practice of justice in the OT, the famous eye for na eye, tooth for a tooth. It presents aids for the interpretation of curses in the Psalms; makes an analysis of the current stateof the question; verifies the coherence or incoherence of the term imprecatory Psalm ; treats the difficult question of the historical context of the Psalms; and, more, highlights certain points which create difficulties for the Christian interpretation of this type of literature. It treats questions of text, of structure, of literary genre, of authorship, and of the context of Psalm 137 in life and history. Further, it presents parallels to this genre in the Biblical world and compares versions of Psalm 137 in Portuguese. It shows that in the OT a word was treated as having intrinsic power; it verifies how, normally, curses were used in the OT in general, preparing the way for the verification of its specific use in Psalm 137; it brings together a rapid historical retrospective showing the long trajectory of the conflicts of Isarael/ Judah with Edom and Babylon, which leads the Psalmist to feel he has the right to ask that these two nations be destroyed and suffer; it also raises the possibility that Psalm 137 is not the only one in the Psalter to contain curses against Edom and Babylon, and poi8nts out that in this composition there are one self-curse and two curses, one against Edom and the other against Babyolon, all of them taking into consideration the principal of reciprocitgy in OT justice.(AU)